Need Assessment For Learning App Implementation to Introduction Mobile Application Based on Mobile Learning - RianFartaWijaya, Ganefri, Fahmi Rizal, Nova Mayasari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Purpose of the study was to analyse the Need of the Implementation of Mobile application based on mobile learning. This study used Survey Method, and the research subjects were fitfth (5) semester students of Computer System program of the Pembangunan Panca Budi University Medan. In collecting Data, the reaserchers used indirect communication Techniques, by using questionnaires, and Descriptive analysis was used as the data analysis technique. The result of the study are: (1) out of forty (40) students as respondents, all of them agree with the implementation of learning application based on learning mobile. It is because it can help students to study easily wherever and whenever they are. (2) the obstacle that may occur is the students' phone storage capacity is insufficient to run the learning application because of 25% memory has been used.